The social function of science - Bernal, J. D. (M.I.T. Press, 1939)
It was a groundbreaking treatise both in exploring the scope of science and technology in fashioning public policy, with Bernal arguing that science is the chief agent of change in society, and in devising policies that would optimize the way science was organized. The sense of impending war clearly emerges. Bernal deplored the application of scientific discoveries in making war ever more destructive, while acknowledging that the majority of scientific and technical breakthroughs have their origins in military exigencies, both because of the willingness to spend money and the premium placed on novelty during wartime.'